Why Muslim Countries under developed? - Aisyah, Siti (AL-IKTISAB: Journal of Islamic Economic Law, 2017)
Islam is very comprehensive religion as the way of life that guides mankind in all aspects of life. The two responsible of human such as worshiper of Allah and agent of economic on earth are related to development. Nowadays, the development of Islamic economic and finance in many Muslim countries is significant to contribute the economic growths in the country in spite of many of Muslim countries are still in the poverty problem. By then, the paper attempts to analyze the major problem of Muslim countries toward development, to explore determinant factors of development in Islamic golden age and to give best solution to economic development of Muslim countries. It is qualitative research by using content analysis to answer all reseach questions. The findings are that The problem of development in Muslim countries is very complex such as poverty, lack of human skill, income inequality, low level productivity, accumulation of foreign debt and illiteracy. There are several countries that have excessive oil can be categorized as high human development. The economic development of Islamic Golden age applies religious and physical factors to promote society welfare. Lastly, there are five successfull determinant factors in economic development such as religion, knowledge, wealth, inovation and institution.